Dialogic space in three lower primary classrooms a multimodal approach - Amasha, Siti Azlinda (2018)
This thesis uses a multimodal approach to explore how three lower primary teachers manage dialogic space in their respective classrooms during the Shared Book Approach (SBA) lessons, where they read big books to their students while holding whole class discussions.